Proteome of human plasma very low-density lipoprotein and low-density lipoprotein exhibits a link with coagulation and lipid metabolism - Dashty, M; Motazacker, M M; Levels, J; de Vries, M; Mahmoudi, M; Peppelenbosch, M P; Rezaee, F (Thrombosis and haemostasis, 2014)
Apart from transporting lipids through the body, the human plasma lipoproteins very low-density lipoprotein (VLDL) and low-density lipoprotein (LDL) are also thought to serve as a modality for intra-organismal protein transfer, shipping proteins with important roles in inflammation and thrombosis from the site of synthesis to effector locations. To better understand the role of VLDL and LDL in the transport of proteins, we applied a combination of LTQ ORBITRAP-XL (nLC-MS/MS) with both in-SDS-PAGE gel and in-solution tryptic digestion of pure and defined VLDL and LDL fractions. We identified the presence of 95 VLDL- and 51 LDL-associated proteins including all known apolipoproteins and lipid transport proteins, and intriguingly a set of coagulation proteins, complement system and anti- microbial proteins. Prothrombin, protein S, fibrinogen γ, PLTP, CETP, CD14 and LBP were present on VLDL but not on LDL. Prenylcysteine oxidase 1, dermcidin, cathelicidin antimicrobial peptide, TFPI-1 and fibrinogen α chain were associated with both VLDL and LDL. Apo A-V is only present on VLDL and not on LDL. Collectively, this study provides a wealth of knowledge on the protein constituents of the human plasma lipoprotein system and strongly supports the notion that protein shuttling through this system is involved in the regulation of biological processes. Human diseases related to proteins carried by VLDL and LDL can be divided in three major categories: 1 - dyslipidaemia, 2 - atherosclerosis and vascular disease, and 3 - coagulation disorders.